2011
DOI: 10.1007/s10689-011-9505-3
|View full text |Cite
|
Sign up to set email alerts
|

RB1 mutations and second primary malignancies after hereditary retinoblastoma

Abstract: Survivors of hereditary retinoblastoma have a high risk of second primary malignancies, but it has not been investigated whether specific RB1 germline mutations are associated with greater risk of second primary malignancies in a large cohort. We conducted a retrospective cohort study of 199 survivors of hereditary retinoblastoma with a documented RB1 germline mutation diagnosed between 1905 and 2005. In total, 44 hereditary retinoblastoma survivors developed a second primary malignancy after a median follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 30 publications
1
60
1
Order By: Relevance
“…In three of these families, one of the RB1 carriers without Rb had developed a sarcoma that may be RB1 -related. In a previous study, we have shown that the risk of a second cancer for carriers of a incomplete penetrance RB1 mutation is much lower than for carriers of a mutation with high penetrance 20. Nevertheless, awareness of a possible increased risk is important, and therefore RB1 mutation testing of family members can be useful even when they will not develop Rb anymore.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In three of these families, one of the RB1 carriers without Rb had developed a sarcoma that may be RB1 -related. In a previous study, we have shown that the risk of a second cancer for carriers of a incomplete penetrance RB1 mutation is much lower than for carriers of a mutation with high penetrance 20. Nevertheless, awareness of a possible increased risk is important, and therefore RB1 mutation testing of family members can be useful even when they will not develop Rb anymore.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all newly diagnosed Rb patients have been offered DNA testing since the beginning of the 1990s and extensive follow-up procedures have led to the testing of virtually all Rb patients still living from the Dutch National Retinoblastoma Register 20. Our study cohort thus forms a unique unbiased nationwide group of Rb patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, with improved therapy and better survival for their RBs it has become clear that these individuals have an increased risk of other cancers later in life as well. 107 Somatic alterations of RB1, including large deletions and promoter methylations, have been detected in different cancer forms, including breast cancer (see references in Berge et al 108 ). In a recent paper, Witkiewicz et al 109 found an RB-deficiency gene expression signature to be associated with increased chance of a pathological complete response among breast cancer patients receiving primary chemotherapy with 5-fluorouracil, adriamycin and cyclophosphamide, but also patients treated with combined anthracycline-and taxane-containing regimens.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%
“…Intra-and interfamily variation in phenotypic expressivity suggests there may be other modifying factors (32,33). In a large retrospective cohort of RB survivors, individuals with lower penetrance mutations were also found to have a lower risk of second primary malignancies (34).…”
Section: Hereditary Rb: Introductionmentioning
confidence: 99%